2019
DOI: 10.1371/journal.pone.0223944
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intravitreal ziv-aflibercept in choroido-retinal vascular diseases: A randomised double-blind intervention study

Abstract: AimTo evaluate the safety of 1.25mg and 2mg intravitreal ziv-aflibercept (IVZ) in Ghanaian eyes with choroido-retinal vascular diseases.DesignProspective, randomised, double blind, interventional study.MethodsTwenty patients with centre involving macular oedema in diabetic retinopathy, retinal vein occlusion, and neovascular age-related macular degeneration were assigned to 2 groups receiving 3 doses of 1.25mg/0.05ml (group 1) and 2mg/0.08ml IVZ (Group 2) at 4 weekly intervals. Safety data was collected after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…5 , 8 , 13 , 17 Studies have also been performed using 2 mg/0.08mL and 2.5 mg/0.1mL, and no differences were found regarding safety and effectiveness compared to 1.25 mg/0.05 mL. 9 , 10 , 16 , 18–20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 , 8 , 13 , 17 Studies have also been performed using 2 mg/0.08mL and 2.5 mg/0.1mL, and no differences were found regarding safety and effectiveness compared to 1.25 mg/0.05 mL. 9 , 10 , 16 , 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Baghi et al found a reduction in central macular thickness (313±120 μm) also very similar to results found in our study using Ziv-aflibercept (324 ± 114 μm). 18 …”
Section: Discussionmentioning
confidence: 99%
“…Disease activity recurrence was defined as a macula that is dry (absence of IRF and SRF) followed by the observation of fluid at subsequent visits, BCVA loss of at least one line on the VA chart with evidence of fluid in the macula or increase in CSFT of at least 100 lm on OCT. IVZ IVZ was administered as per institutional protocol. Details of the protocol for the preparation of IVZ prior to intravitreal injection have been reported previously [19]. The intravitreal injection is done using a sterile technique.…”
Section: Methodsmentioning
confidence: 99%
“…IVZ was administered as per institutional protocol. Details of the protocol for the preparation of IVZ prior to intravitreal injection have been reported previously [ 19 ]. The intravitreal injection is done using a sterile technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation